Utilizing Consumer Behavior to Form Hospital Marketing Strategies during the Covid-19 Pandemic: a Scoping Review - Listya Tresnanti Mirtha; Wachyu Sulistiadi (Syntax Idea)
A critical situation can substantially impact human behavior, resulting in irreversible behavioral changes. Given the interdependence between various economic aspects and public health measures, including lockdowns, national economies have become unstable, signifying a transformation in market dynamics. The authors aimed to gain a deeper understanding of consumer behavior in the context of the COVID-19 pandemic, recognizing that crises often lead to alterations in consumer behavior patterns. We searched eight databases - CINAHL, Cochrane Library, Embase, EmCare, JBI EBP, Medline, Scopus, and PsycInfo. Out of 366 titles and abstracts, twenty-four papers were selected. In an observational study, 11 (45.8%) publications were conducted in hospitals, clinics, and communities. Meanwhile, the rest of the studies were carried out in various other healthcare institutions. Consumer behavior and using technology as marketing tools during the COVID-19 pandemic were the most commonly explored topics. The hospital-at-home model illustrates how healthcare institutions can undertake significant strategic initiatives to usher in comprehensive reforms that prioritize consumers and transform care delivery. The persistent drive to employ digital technology for enhancing the quality of healthcare services and reducing costs serves as a constant motivation. This implies that the consistent effort to harness digital technology to enhance healthcare service quality and reduce expenses has been a steady impetus. Further research is required to ascertain the long-term effectiveness and suitable strategies for optimizing advantages while mitigating risks in the COVID-19 pandemic. A more comprehensive approach would include taking patients' perspectives on using digital health technologies and addressing specific challenges, ethical considerations, and drawbacks highlighted in the existing literature.